2014
DOI: 10.1098/rsif.2014.0641
|View full text |Cite
|
Sign up to set email alerts
|

Ants work harder during consensus decision-making in small groups

Abstract: Individuals derive many benefits from being social, one of which is improved accuracy of decision-making, the so-called 'wisdom of the crowds' effect. This advantage arises because larger groups can pool information from more individuals. At present, limited empirical data indicate that larger groups outperform smaller ones during consensus decision-making in human and non-human animals. Inaccurate decisions can lead to significant costs, and we might therefore expect individuals in small groups to employ mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 61 publications
2
19
1
Order By: Relevance
“…3b), although these factors were also linked. As in previous studies (Cronin 2014;Cronin & Stumpe 2014), quorum thresholds were higher in larger colonies (Table 2). There was also a colony size effect on the proportion of active ants, with the one smaller colony (B) having a notably higher proportion of active ants (Fig.…”
Section: Intercolony Differences In Relocation Metricssupporting
confidence: 86%
See 1 more Smart Citation
“…3b), although these factors were also linked. As in previous studies (Cronin 2014;Cronin & Stumpe 2014), quorum thresholds were higher in larger colonies (Table 2). There was also a colony size effect on the proportion of active ants, with the one smaller colony (B) having a notably higher proportion of active ants (Fig.…”
Section: Intercolony Differences In Relocation Metricssupporting
confidence: 86%
“…Intracolony heterogeneity in behaviour ('division of labour') is well known in social insects and is usually linked with genetic composition, size or age structure of colonies (H€ olldobler & Wilson 1990;Jeanson & Weidenm€ uller 2014). However, while colony size is known to influence collective processes in M. nipponica (Cronin 2014;Cronin & Stumpe 2014), colonies in this study were in most cases of similar size and, where different, did not vary in a manner consistent with a colony size effect (for example, the largest and smallest colonies exhibited the most similarity in performance characteristics). Similarly, this species is monogynous and monandrous (Murakami et al 2000), and thus variation between individuals is unlikely to have a genetic basis.…”
Section: Discussionmentioning
confidence: 99%
“…This result provides strong supporting evidence for this model and its assumptions. Importantly, it implies that the cooperative motion is not a wisdom-of-the-crowds phenomenon (25) in which the forces of a large number of poorly informed ants average out to increase overall accuracy (26,27). Such averaging behavior could result in fluctuations of the load around the direction to the nest (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because migration stage is a categorical variable, we recoded it as a series of dummy variables so that it could be included in regression analysis. We also tested whether accuracy was influenced by colony size, measured as number of workers, number of brood items, total colony population, and the ratio of brood to workers, as previous research has shown that these factors can influence decision making (Donaldson-Matasci and DeGrandi-Hoffman 2013; Schaerf et al 2013;Cronin and Stumpe 2014). Each colony size variable was included in the model to determine if it provided any additional predictive value compared with the model with migration stage only, and if not, it was removed from the model.…”
Section: Discussionmentioning
confidence: 99%